The identity of Accipiter cirrocephalus rosselianus Mayr, 1940 - Schodde, Richard (Zootaxa, 2015)
Mayr (1940) described the subspecies Accipiter cirrocephalus rosselianus of the Collared Sparrowhawk from two specimens in juvenile (first-year) plumage collected on Rossel (Yela) Island, in the Louisiade Archipelago off southeast New Guinea. They are still the only specimens of this form known from the Louisiade Archipelago, and were taken in March 1898 and December 1915 by the renowned Rothschild collector Albert S. Meek, who sexed them as males. Mayr (l.c.) presumed their specific identity and stated that rosselianus differed from juveniles of its sister subspecies, A. c. papuanus Rothschild & Hartert, 1913 of mainland New Guinea, in the bolder, browner chevroning of the ventrum, darker dorsal plumage with broad rufous feather edging, and distinctively large size. The large size of the specimens, in fact, raises the question of missexing, because they approach female papuanus in wing (Mayr l.c.). Nevertheless, the collector Meek was careful and experienced in sexing birds (Mayr l.c.) and had recorded both specimens as males on separate occasions. In accord with data presented below, it is evident that the specimens were correctly sexed as males.